Nucleus accumbens core dopamine signaling tracks the need-based motivational value of food-paired cues - Aitken, Tara J. (J Neurochem, 2016)
Environmental reward-predictive stimuli provide a major source of motivation for instrumental reward-seeking activity and this has been linked to dopamine signaling in the nucleus accumbens (NAc). This cue-induced incentive motivation can be quite general, not restricted to instrumental actions that earn the same unique reward, and is also typically regulated by one’s current need state, such that cues only motivate actions when this is adaptive. But it is unknown whether cue-evoked dopamine signaling is similarly regulated by need state. Here we used fast-scan cyclic voltammetry to monitor dopamine concentration changes in the NAc core of rats during a Pavlovian-to-instrumental transfer (PIT) task in which the motivating influence of two cues, each signaling a distinct food reward (sucrose or food pellets), over an action earning a third unique food reward (grape-flavored polycose) was assessed in a state of hunger and of satiety. Both cues elicited a robust NAc dopamine response when hungry. The magnitude of the sucrose cue-evoked dopamine response correlated with the PIT effect that was selectively induced by this stimulus. Satiety attenuated these cue-evoked dopamine responses and behavioral responding, even though rats had never experienced the specific food rewards in this state. These data demonstrate that cue-evoked NAc core responses are sensitive to current need state, one critical variable that determines the current adaptive utility of cue-motivated behavior.